2013
DOI: 10.1093/geront/gnt169
|View full text |Cite
|
Sign up to set email alerts
|

Missing Work After Retirement: The Role of Life Histories in the Retirement Adjustment Process

Abstract: Purpose of the Study:Although the process of adjustment to retirement is often assumed to be related to experiences earlier in life, quantitative empirical insights regarding these relationships are limited. This study aims to improve our understanding of adjustment to the loss of the work role, by conceptualizing retirement as a multidimensional process embedded in the individual life course.Design and Methods:Analyses are based on panel data collected in 2001, 2006–2007, and 2011 among Dutch retirees (N = 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 37 publications
1
43
0
4
Order By: Relevance
“…Retirees without a partner (e.g., because of a divorce) are a vulnerable group in the retirement process. Earlier research has shown, for instance, that they are relatively likely to miss the social contacts and social status of work after retirement (Damman, Henkens, & Kalmijn, 2015). The findings of the current study show that rather these retirees -those without a partner -experience a relatively high level of support from their children upon retirement, as well as retirees who have a poor financial situation.…”
Section: Discussionmentioning
confidence: 44%
“…Retirees without a partner (e.g., because of a divorce) are a vulnerable group in the retirement process. Earlier research has shown, for instance, that they are relatively likely to miss the social contacts and social status of work after retirement (Damman, Henkens, & Kalmijn, 2015). The findings of the current study show that rather these retirees -those without a partner -experience a relatively high level of support from their children upon retirement, as well as retirees who have a poor financial situation.…”
Section: Discussionmentioning
confidence: 44%
“…Managing retirement is a central developmental task in late adult life involving two developmental challenges. The first challenge involves the social and psychological detachment from work (Damman, Henkens, & Kalmijn, 2015). The second involves the development of a satisfactory post-retirement lifestyle (Havighurst, Munnichs, Neugarten, & Thomae, 1969).…”
Section: Effects Of Three Types Of Retirement Preparation Program: a mentioning
confidence: 99%
“…Even though these qualitative studies suggest that earlier life experiences are of importance for understanding subjective processes surrounding the act of retirement, insights into these relationships based on quantitative studies are still scarce. Existing studies suggest that both work career experiences (e.g., career path) and marital histories are associated with differences between retirees in terms of their retirement satisfaction (Price andJoo 2005, Quick andMoen 1998) and the extent to which they miss aspects of work after retirement (Damman et al 2013b). For example, divorced retirees without a partner have been found to be more likely to miss the social dimensions of work (i.e., social contacts and social status) compared with continuously married retirees, and those who repartnered after divorce are more likely to miss financial resources (Damman et al 2013b).…”
Section: Life Histories and Subjective Processes Surrounding Retirementmentioning
confidence: 99%